SOCIAL MEDIA ANALYTICS OF BOOSTER VACCINE COVID-19 DISCOURSE ON TWITTER - Ciptadi, Suluh Gembyeng; Marzuki, Alfath (The Sunan Ampel Review of Political and Social Sciences, 2023)
People around the world are currently carrying out booster vaccinations in the midst of the outbreak of the Omicron variant of the COVID-19 virus. In Indonesia, vaccine booster activities have been carried out since January 12, 2022. The Indonesian government makes vaccines free and encourages the public to immediately carry out vaccine booster. Vaccine booster information and campaigns also appear on social media. Twitter as one of the social media that is widely used in Indonesia is also enlivened with discussions about vaccine boosters. The objective of this research is to see how the vaccine booster issue is discussed on Twitter. By using the concept of Social Media Analytics (SMA), this study explores tweet data and analyzes it based on the hashtags that appear, the accounts that post a lot and get re-tweets, and the accounts that are mentioned the most (mentioned) in the discussion of the vaccine booster issue. The method of this research is descriptive qualitative. Data from Twitter will be collected from February to March 2022. Data will be collected using NVivo Plus 12 software. The result expected to provide social media analysis related to “Booster Vaccine” discourse that occurred in twitter.